2023
DOI: 10.3390/buildings13051312
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic and Probabilistic Risk Management Approaches in Construction Projects: A Systematic Literature Review and Comparative Analysis

Abstract: Risks and uncertainties are inevitable in construction projects and can drastically change the expected outcome, negatively impacting the project’s success. However, risk management (RM) is still conducted in a manual, largely ineffective, and experience-based fashion, hindering automation and knowledge transfer in projects. The construction industry is benefitting from the recent Industry 4.0 revolution and the advancements in data science branches, such as artificial intelligence (AI), for the digitalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 133 publications
0
14
0
Order By: Relevance
“…Song et al [22] advocated for sustainable construction practices to minimize environmental impact and promote long-term economic viability. Khodabakhshian et al [23] highlighted the importance of lifecycle costing in assessing the total cost of ownership over a project's lifecycle, including construction, operation, and maintenance costs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Song et al [22] advocated for sustainable construction practices to minimize environmental impact and promote long-term economic viability. Khodabakhshian et al [23] highlighted the importance of lifecycle costing in assessing the total cost of ownership over a project's lifecycle, including construction, operation, and maintenance costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies involving the fuzzy integrated Delphi-ISM-MICMAC hybrid MCDM model have demonstrated its effectiveness in addressing complex decision-making problems across various domains. Fuzzy sets are a mathematical approach that the handles uncertainty and imprecision in decision-making processes by assigning degrees of membership to linguistic terms [23]. In the context of MCDM, fuzzy sets enable decision-makers to express subjective preferences and uncertainties in a quantitative manner, facilitating the integration of qualitative and quantitative criteria in decision-making models [24].…”
Section: Previous Studies Involving the Fuzzy Integrated Delphi-ism-m...mentioning
confidence: 99%
See 3 more Smart Citations